Portrety ludzi i zwierząt w powieści detektywistycznej Marty Matyszczak Tajemnicza śmierć Marianny Biel - Szulik -Opala, Tatiana (Paidia i Literatura, 2020)
The article points to the advantages of utilizing books chosen and read by students during lessons of Polish. As illustrative example here serves Tajemnicza śmierć Marianny Biel written by Marta Matyszczak, a contemporary detective novel, published in 2017, partially narrated from the perspective small invalid mongrel. The novel’s structure is conducive to discussion of detective stories in didactic work, showing the “Silesian” features of the novel’s characters, and analyzing their seemingly superficial characters. On the basis of the novel, the subject of animal studies may be raised: the animality of the relationship between humans and animals. The article draws attention to the importance of the animal issues in humanities, going beyond the understanding thereof as “the animality of human nature.” It emphasizes the essence of giving voice to the animals and empowering them, without trying to “humanize” them.